Optimalization of Water for Nursery and Rearing of Asian Redtail Catfish (Mystus nemurus C.V) - Mulyadi Mulyadi; Niken Ayu Pamukas (Jurnal Natur Indonesia, 2023)
Fish culture activities usually release wastes to environments such as faeces, urine, uneaten food and other by-product metabolism activities. For increased water quality, ideally in aquaculture media, various methods could be used, such as filtering techniques and sinking and dissolving methods. Various filter materials could be used to increase water quality, such as silt, gravel, charcoal, coconut shell, palm fiber, and zeoliteThe study on the effect of recirculation systems using various filter materials and aquaponic systems on water quality has been carried out. Several filter materials were used in four kinds of treatment,  namely aquarium using aerators (control), aquarium using silt, gravels and palm fiber (recirculation), aquarium using mustard greens (aquaponic system) and aquarium using spoons (recirculation). The study results showed that different filter materials significantly affected nitrate and nitrite concentration in the catfish culture media. It was invented that the treatment of a recirculation system combined with an aquaponic system could increase water quality parameters such as  CO2 (7.99 - 11.98 mg.L-1), NH3 (0.02 - 0.07 mg.L-1), NO2 (2.43 - 0.02 mg.L-1), NO3 (4.32 - 0.04 mg.L-1) respectively. Still, the other water quality parameters were similar. The best results were achieved at the same treatment, namely absolute growth rates  (4.01 g), daily growth rates  (1.96 %) and survival rates (91.11 %), respectively